1988
DOI: 10.1029/rs023i003p00299
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric imaging using computerized tomography

Abstract: Computerized tomography (CT) techniques can be used to produce a two‐dimensional image of the electron density in the ionosphere. The CT problem requires that the measured data be the line integral through the medium of the unknown parameter; transionospheric satellite beacon total electron content data recorded simultaneously at multiple ground stations fulfill this requirement. In this paper the CT problem is formulated as it applies to ionospheric imaging and limitations of the technique are investigated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
217
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(220 citation statements)
references
References 13 publications
0
217
0
3
Order By: Relevance
“…[4] During the years, the researchers have developed and used other means to gather information on the upper ionosphere and plasmasphere, such as: coherent scatter radar observations of underdense electron density irregularities [Booker, 1956;Greenwald, 1996], incoherent scatter radar probing [Bowles, 1958;Gordon, 1958;Farley, 1996], observations using topside sounders onboard satellites [Franklin and Maclean, 1969;Reinisch et al, 2001], in situ rocket and satellite observations [Pfaff, 1996], tomography [Austen et al, 1988;Leitinger, 1996b], and occultation measurements [Phinney and Anderson, 1973; Leitinger, 1996b]. There is no universal method; each type has advantages as well as shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…[4] During the years, the researchers have developed and used other means to gather information on the upper ionosphere and plasmasphere, such as: coherent scatter radar observations of underdense electron density irregularities [Booker, 1956;Greenwald, 1996], incoherent scatter radar probing [Bowles, 1958;Gordon, 1958;Farley, 1996], observations using topside sounders onboard satellites [Franklin and Maclean, 1969;Reinisch et al, 2001], in situ rocket and satellite observations [Pfaff, 1996], tomography [Austen et al, 1988;Leitinger, 1996b], and occultation measurements [Phinney and Anderson, 1973; Leitinger, 1996b]. There is no universal method; each type has advantages as well as shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…As the ionospheric total electron content (TEC) is an integrated value of the ionospheric electron density along a ray path of the radio signal from a satellite to a ground receiver, the problem to reconstruct the electron density profile from a set of the TEC values is a kind of computerized tomography (CT). Since Austen et al, [4] applied the algebraic reconstruction technique (ART) to the twodimensional analysis of model TEC data generated by a computer simulation various methods for CIT were proposed and applied to analyses of model data and real observation data. Though the two-dimensional ionospheric tomography has been studied extensively from both the theoretical and observational aspects [5][6][7], in these studies only the ionospheric structure within a cross-section defined by the satellite orbit and the ground receiver array can be obtained, which limits strongly the observation time and place.…”
Section: Computerized Ionospheric Tomographymentioning
confidence: 99%
“…The use of tomographic methods for ionospheric research was first suggested by (Austen et al, 1988). (Bust and Mitchell, 2008) provide a good overview on the development of the topic.…”
Section: Introductionmentioning
confidence: 99%